Genome-wide identification of the opsin protein in Leptosphaeria maculans and comparison with other fungi (pathogens of Brassica napus) - Mohri, Marzieh; Moghadam, Ali; Burketova, Lenka; Ryšánek, Pavel (Frontiers in Microbiology, 2023)
The largest family of transmembrane receptors are G-protein-coupled receptors (GPCRs). These receptors respond to perceived environmental signals and infect their host plants. Family A of the GPCR includes opsin. However, there is little known about the roles of GPCRs in phytopathogenic fungi. We studied opsin in Leptosphaeria maculans, an important pathogen of oilseed rape (Brassica napus) that causes blackleg disease, and compared it with six other fungal pathogens of oilseed rape. A phylogenetic tree analysis of 31 isoforms of the opsin protein showed six major groups and six subgroups. All three opsin isoforms of L. maculans are grouped in the same clade in the phylogenetic tree. Physicochemical analysis revealed that all studied opsin proteins are stable and hydrophobic. Subcellular localization revealed that most isoforms were localized in the endoplasmic reticulum membrane except for several isoforms in Verticillium species, which were localized in the mitochondrial membrane. Most isoforms comprise two conserved domains. One conserved motif was observed across all isoforms, consisting of the BACTERIAL_OPSIN_1 domain, which has been hypothesized to have an identical sensory function. Most studied isoforms showed seven transmembrane helices, except for one isoform of V. longisporum and four isoforms of Fusarium oxysporum. Tertiary structure prediction displayed a conformational change in four isoforms of F. oxysporum that presumed differences in binding to other proteins and sensing signals, thereby resulting in various pathogenicity strategies. Protein–protein interactions and binding site analyses demonstrated a variety of numbers of ligands and pockets across all isoforms, ranging between 0 and 13 ligands and 4 and 10 pockets. According to the phylogenetic analysis in this study and considerable physiochemically and structurally differences of opsin proteins among all studied fungi hypothesized that this protein acts in the pathogenicity, growth, sporulation, and mating of these fungi differently.